Effects of Organizational Culture and Pay Levels on Employee Retention: Focused on Generational Difference - Myeongju Lee; Kyetaik Oh; Hyunok Kim (Administrative Sciences)
Research on generational differences in the workplace is important as it leads to more effective recruitment, retention, and employee wellbeing in terms of human resource management. This study investigates whether there are differences in perceptions of turnover intention, pay level, and organizational culture between different generational groups. First, this study identifies the relationship between pay level and turnover intention. Second, it confirms the moderating effect of organizational culture on the relationship between pay level and turnover intention. Finally, a three-way interaction analysis was conducted to determine whether these relationships differed between Baby Boomers, Gen Xers, and Millennials. As a result of the empirical analysis, the millennial generation showed higher turnover intention than other generations. It was confirmed that the effect of hierarchical culture was greater than that of pay level on the decrease in turnover intention in the millennial generation than in other generations. In other words, it was found that as the hierarchical culture weakened, the turnover intention of Millennials decreased more significantly than that of other generations. Based on these findings, we propose recommendations for understanding Millennials in the workplace and managing generational diversity.